2011
DOI: 10.1002/anie.201105289
|View full text |Cite
|
Sign up to set email alerts
|

The Deformability of Polymers: The Role of Disordered Mesomorphic Crystals and Stress‐Induced Phase Transformations

Abstract: Isotactic polypropylene (iPP) is of enormous and still increasing commercial importance because of its favored combinations of properties, such as good rigidity, high thermal resistance, low density, and ease of processability, which can be achieved at relatively low costs.[1] The wide range of applications of iPP results from its versatility and the variety of possible modifications of the basic material, which already starts in the polymerization reactor [1] and can be further achieved during crystallizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(89 citation statements)
references
References 25 publications
(27 reference statements)
2
87
0
Order By: Relevance
“…For all materials, similar trends are observed for similar cooling conditions. It is seen that the modulus of the g-crystal phase and the mesomorphic phase materials is lower than for the a-crystal phase material, which was also observed in other studies [30]. The reason for this is the reduced crystallinity.…”
Section: Methodssupporting
confidence: 80%
See 1 more Smart Citation
“…For all materials, similar trends are observed for similar cooling conditions. It is seen that the modulus of the g-crystal phase and the mesomorphic phase materials is lower than for the a-crystal phase material, which was also observed in other studies [30]. The reason for this is the reduced crystallinity.…”
Section: Methodssupporting
confidence: 80%
“…Another study showed that for i-PP's with similar crystallinities the a-crystal phase was ductile with an elongation-at-break of 300%, an elongation-at-break of over 600% for the mesomorphic phase and an elongation-at-break of over 1000% for the g-crystal phase, which was explained in terms of a phase transition from the g-crystal phase to the mesomorphic phase during deformation [30]. A study on the effect of stereoregularity of i-PP on the crystal phase formation showed that the mechanical properties of i-PP can be tuned using metallocene catalysts [31].…”
Section: Introductionmentioning
confidence: 99%
“…The plastic deformation of unoriented films of Figure 3 and the elastic recovery observed in the stress–strain curves of Figure 5 are associated with polymorphic transformations that occur during stretching and relaxation 29, 36, 37. For the more stereoregular non‐elastic samples iPP( 1 )–iPP( 4 ), the α or γ forms of slowly crystallized samples transform by stretching at high deformations in the mesomorphic form,36, 37 whereas in quenched mesomorphic samples, no structural transformations generally occurs during stretching and only orientation of the mesomorphic crystals occurs 39. An example is shown in Figure 6 for the sample iPP( 3 ) with 3.7 mol% of rr defects.…”
Section: Resultsmentioning
confidence: 99%
“…More stereoirregular samples iPP( 4 ) and iPP( 5 ) with concentrations of rr defects of 5.9% and 11%, respectively, show instead unexpected better ductility when slowly crystallized from the melt in the γ form than when crystallized in the nodular solid mesophase (Figure 3). 39…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation